Contralateral suppression of otoacoustic emissions in a clinical sample of children with auditory processing disorder. (4th May 2019) - Mattsson, Tone Stokkereit; Lind, Ola; Follestad, Turid; Grøndahl, Kjell; Wilson, Wayne; Nordgård, Ståle
Abstract: Objective: The suppression of evoked otoacoustic emissions (EOAE) may serve as a clinical tool to evaluate the medial olivocochlear (MOC) reflex, which is thought to aid speech discrimination (particularly in noise) by selectively inhibiting cochlear amplification. The present study aimed to determine if contralateral transient evoked otoacoustic emission (TEOAE) suppression was present in a clinical sample of children with listening difficulties with and without auditory processing disorder (APD). Design: A three-group, repeated measure design was used. Study sample: Forty three children aged 8–14 years underwent an auditory processing assessment and were divided into three groups: children with reported listening difficulties with APD, children with reported listening difficulties without APD, and children with normal hearing. APD was defined as per British Society of Audiology. Results: TEOAE suppression was present in all three participant groups. No significant group, age or ear effects were observed for TEOAE suppression in dB or as a normalised index. Conclusion: Contralateral TEOAE suppression method could not be used as a clinical tool to identify APD in this study's participating children and did not support the hypothesised link between reduced MOC function and general listening difficulties in background noise in children with or without APD.